(untitled) (Italian Journal of Public Health, 2004)
A brief review is presented on the value of bacterial indicators in assessing the safety of water. No single microbial indicator parameter is adequate to determine the water quality in all circumstances. Thus, it is necessary to gain a better understanding of the usefulness of the traditional parameters for water monitoring and the methods available for their analysis.